Radio documentary – problems with contemporary genre terminology - Monika Białek (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
Looking at the various definitions of radio documentary found in academic literature, several common elements can be found which typify the genre. These are: sound as the main constructional element, authentic events constituting the starting point, stress on the aesthetic quality of the relation, the considered authorial concept and its functioning through the medium of radio. In the last two decades, alongside the hitherto functioning and recognised terms applied in relations to radio news reporting, have appeared new ones: the feature; documentary programme/documentary radio broadcast/fictional radio broadcast/docudrama; radionovel; news blogs. In the age of new media, convergent forms have also appeared, among which we should mention: photocasts; multireports; sound maps. This situation means that it’s worth thinking about the hitherto genres, because they seem to be insufficient in the current media situation. Hence, the article presents a proposal for a typology of artistic aural forms. It presents a division based on the channel used to deliver the message, the means of production and governing function.